The virus made me lose control: The impact of COVID-related work changes on employees’ mental health, aggression, and interpersonal conflict - Han, Changlin; Zhang, Ruyi; Liu, Xiyao; Wang, Xueling; Liu, Xiaotong (Frontiers in Public Health, 2023)
COVID-related work changes have seriously disrupted employees’ familiar routines and hampered their lives and work. Although this topic has drawn rising attention, to our best knowledge, there is limited studes have investigated the impact of COVID-related work changes on employees’ mentality and behavior. In this paper, we developed a moderated mediation model based on ego depletion theory to test how and when COVID-related work changes impact employees’ mental health, interpersonal conflict, and aggression behavior. Building upon the analysis of 536 samples collected from a large Chinese manufacturing company, we found that COVID-related work changes significantly increase employees’ ego depletion and; while with the mediating effect of ego depletion, COVID-related work changes harm employees’ mental health and boost their interpersonal conflict and aggression. Moreover, trait resilience has an intervention in COVID-related work changes and employees’ ego depletion, which weakens the indirect impact of COVID-related work changes on mental health, interpersonal conflict, and aggression. In practice, we suggest that managers should take measures to improve the employees’ mental status and avoid conflicts promptly while taking steps to keep organizations on track.